Developmental and Professional-Social Impact on Women’s Unconditional Self-Acceptance, Well-being and Quality of Life - Maystruk, Viktoriia (Psychological Prospects Journal, 2017)
The results of theoretical and empirical analysis of woman’s unconditional self-acceptance as a factor of her psychological well-being and quality of life are highlighted in the article. Unconditional self-acceptance is viewed from rational emotive behavioral therapy perspective and defined as self-worth as basis for accepting attitude towards oneself notwithstanding the approval of others. Psychological well-beingcontains autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, self-acceptance. Quality of life is represented by objective (income, occupation), and subjective (values, emotional well-being) aspects. The results of empirical study show the developmental and professional differences between indices of unconditional self-acceptance among women with age 20–40 years and 40–60 years. The indices of unconditional self-acceptance become higher with age, professional and social growth. The most developed aspects of quality of life in women with age 20–40 years are represented by own health, relatives’ health and social support. The most developed aspect of quality of life in women with age 40–60 years is social support. It is in line with highly developed positive relations with others as psychological well-being component combined with purpose in life and personal growth of the womenwith age 40–60 years. The environmental mastery as the psychological well-being componentis highly developed in the womenwith age 40–60 years.